Evaluation of the operating parameters of a kinetic energy storage for the support of a generating set operating in island mode - Markowski Jaroslaw; Jesionek Krzysztof; Iliev Iliya; Wieczorkiewicz Grzegorz; Dudek Magdalena; Imilkowski Pawel (E3S Web of Conferences)
The development of electric power systems is oriented toward increasing the share of electricity generated from renewable energy sources. These actions lead to the destabilization of the power grid, necessitating the implementation of stabilizing measures such as the temporary disconnection of renewable energy installations, the construction of energy storage systems, and the modernization of thermal energy sources. Modernization changes in electric power systems require significant financial investments and long implementation timelines. As a result, energy distributors are forced to make capital investments, which translate into high energy prices for consumers. For this reason, many companies, in optimizing the cost of their business operations, consider the possibility of operating within so- called isolated energy islands. Typically, this involves isolating the internal power network to supply a portion of the company’s production activities. This approach entails defining an internal power supply area and implementing an energy generation system in the form of a genset – a combustion engine combined with an electric generator. Such a system must ensure frequency stability within the isolated electrical network and provide the required amount of energy for the isolated system. These conditions can be met by a genset capable of generating approximately 150% of the energy demand. This leads to significantly increased investment costs and deteriorated operational conditions for the genset, resulting in reduced energy conversion efficiency.